2008
DOI: 10.1111/j.1440-1681.2008.04963.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anaesthetic Agents on P‐wave Dispersion on the Electrocardiogram: Comparison of Propofol and Desflurane

Abstract: Anaesthetics influence cardiac electrical activity by various mechanisms; thus, they may have pro-arrhythmic or anti-arrhythmic actions. Increased P-wave dispersion is associated with a risk of paroxysmal atrial fibrillation. The aim of the present study was to analyse the impact of propofol and desflurane on changes in P wave dispersion, which may reflect the anti-arrhythmic effects of these drugs. Fifty patients undergoing scheduled surgery were included in the study. Patients were divided into two equal gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…The general anesthetic sevofl urane has been reported to prolong Pwd, while desfl urane has no effect on it, and propofol shortens it 1,48,49 . Pwd intervals also extend after laryngoscopy and tracheal intubation 1 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The general anesthetic sevofl urane has been reported to prolong Pwd, while desfl urane has no effect on it, and propofol shortens it 1,48,49 . Pwd intervals also extend after laryngoscopy and tracheal intubation 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was demonstrated that inhalation anesthetic agents such as desfl urane, sevofl urane, isofl urane, enfl urane or halothane, extend the QTc interval duration 1,3,4,17 . Despite the fact that etomidate and midazolam have no effects on the ventricle repolarization 3,17 , they are not popular drugs for anesthesia induction. Propofol as an intravenous anesthetic agent is a popular choice for anesthesia induction in patients with prolonged QT, QTc, and Pwd interval, since it causes minimal prolongation of QT, QTc, and Pwd interval 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The general anesthetic sevofl urane has been reported to prolong Pwd, desfl urane to have no effect on it, and propofol to shorten it [22][23][24] . At the same time, our literature survey found no study that investigated the effects of local or spinal anesthesia on Pwd.…”
Section: Discussionmentioning
confidence: 99%